Clinical outcomes of patients with unilateral internal derangement of the temporomandibular joint following arthrocentesis and stabilization splint therapy - Hyun-A Heo; Suhyun Park; Sung-Woon Pyo; Hyun-Joong Yoon (SpringerOpen, 2024)
Abstract Background The management of internal derangement (ID) of the TMJ is challenging because of multiple etiologic factors and varying degrees of severity. The aim of this study was to evaluate the clinical outcomes of patients with unilateral ID treated with arthrocentesis and stabilization splint therapy during a 6-month period. Methods A total of 105 patients (87 females, 18 males) with unilateral ID were included in this study. Patients were divided into unilateral anterior disc displacement with reduction (ADDwR) and unilateral anterior disc displacement without reduction (ADDwoR). Patients with ADDwoR were subdivided according to the erosive bone changes. Objective parameters on mandibular movement and subjective parameters on pain were obtained and assessed. Their clinical outcomes before and after arthrocentesis and stabilization splint therapy were compared with the chi-square, Fisher's exact test, paired t-test, or Wilcoxon singed-rank test. Results All objective parameters of unilateral ID patients significantly increased at the 6-month follow-up. The differences in mean visual analog scale (VAS) pain scores were statistically significant in all subjective variables (p < 0.01). In joints with ADDwoR, preoperative maximal mouth opening, and maximal protrusive movement in both groups, with erosive and non-erosive changes were significantly increased after 6 months (p < 0.01). However, right and left maximal lateral movement increased after treatment in both groups but without significant differences. All VAS pain scores on jaw movement and palpation of associated muscles showed a significant decrease regardless of erosive changes. Conclusions The combination of arthrocentesis and subsequent stabilization splint therapy was shown to be highly effective in pain reduction and improvement of mandibular movements in both unilateral ADDwR and ADDwoR, as well as in cases with both erosive and non-erosive bony changes associated with unilateral ADDwoR.